Representations of Palestinian Resistance Between the Honor of Liberation and the Extent of Shortcomings: A Reading in the Experience of the Algerian Poet El-Hacen El-Ouahidi - Rachid, Fouhane (Journal of Ecohumanism, 2024)
This study seeks to explore the poetic experience of the Algerian poet El-Hacen El-Ouahidi, through selected rich examples of his poetry that reflect the writer’s commitment to supporting the Palestinian cause. It reasserts the role of the engaged intellectual in addressing pivotal issues linked to Arab nationalism and reveals the poet’s engagement in this direction by analyzing his stylistic structures. The study sheds light on the structural transformations in the literature of the Palestinian cause, which has become a central issue embraced by poets. El-Ouahidi responds to this cause with profound emotional sensitivity, allowing him to employ stylistic techniques that fulfill deeper artistic functions. These techniques play a role in the poetic context as active agents in the search for self and identity, appealing to the subtleties of aesthetic reception among readers. These include: the phenomenon of multiple styles and purposes, repetition, symbolism, and the diversity and flexibility of poetic segments. Using an analytical stylistic approach, the study raises questions about the extent to which the Palestinian cause is present in El-Hacen El-Ouahidi’s poetry. Was this engagement merely circumstantial and occasional, or was it genuinely spontaneous? How did the poet represent Palestine? What were the dimensions and symbolism that captivated his emotions? What poetic tools did he employ in expressing it? The findings confirm that El-Hacen El-Ouahidi stands as a model of the Algerian poet who is not isolated from the concerns of the Arab nation. He responded to them through his sense of the intellectual’s duty toward Palestine—an issue of the past, present, and future. His interaction with the cause, his dedication to its core concerns, and his focus on its seriousness demonstrate that the Algerian poet continues to engage deeply with the Palestinian issue. It remains his inspiration for writing and a call to defend and confront all who seek to undermine it. Thus, the cause serves as a principal indicator of the commitment of Arab intellectuals to the broader concerns of their nation.